Preferences for tree fruit market attributes among smallholder farmers in Eastern Rwanda - Hanna Ihli; Ronja Seegers; Etti Winter; Brian Chiputwa; Anja Gassner (Agricultural Economics, 2021)
The increasing demand for high-value agricultural products such as fresh fruit presents opportunities for farmers in developing countries due to their higher market value compared with traditional staple crops. This study uses data on trust, risk, and time preferences obtained through behavioral experiments, combined with a discrete choice experiment to understand their effect on farmers' choices of marketing attributes, collecting data from 252 farmers from Eastern Rwanda. The results reveal that farmers, overall, have positive attitudes toward collective marketing channels with guaranteed immediate payments, written contracts, provision of inputs, credit, and training, a personal relationship with a buyer, and low investment costs. Additionally, farmers with lower levels of risk aversion were found to have a greater preference for immediate payment than farmers with higher levels of risk aversion. Farmers with higher future orientation are more likely to choose contracts that guarantee inputs and/or services and written contracts, and they attach lower relative importance to immediate payments than farmers with lower future orientation. Farmers with higher trust levels attach lower relative importance to immediate payments, written contracts, and a personal relationship with a buyer than farmers with lower trust levels.
Keywords: 330; choice experiment; field experiments; marketing preferences; Rwanda; trust risk and time preferences